Binding of the highly toxic tetracycline derivative, anhydrotetracycline, to bovine serum albumin - Burgos, Martha Ines (2011)
Tetracycline (TC) derivatives are extensively used as antibiotics in human and animal medicine and, very recently, they have been screened as anti-amyloidogenic drugs. Anhydrotetracycline (AHTC) is one of the major degradation products of TC that has been linked to several side effects of the drug. We evaluated the interaction of AHTC with bovine serum albumin (BSA), one of the main carriers of amphiphilic molecules in blood, using three complementary analytical methods: fluorescence spectroscopy, isothermal titration calorimetry and differential scanning calorimetry. AHTC bound to BSA with an association constant in the order of 105M1. Drug binding was enthalpically and entropically driven and seemed to involve hydrophobic interactions. AHTC fluorescence enhancement and hypsochromic shifts observed upon binding suggested a low-polarity location excluded from water for the bound drug. Our data are useful for evaluating the biodisponibility of the pharmacophore and the dynamic distribution of the toxic derivative.